Takagi-Sugeno Fuzzy Model Identification for Small Scale Unmanned Helicopter - Arbab Nighat Khizer; Dai Yaping; Syed Amjad Ali; Xu Xiang Yang (Institute of Advanced Engineering and Science, 2014)
This paper presents system identification method for small unmanned helicopter based on Takagi Sugeno fuzzy models under hover. Firstly,the nonlinear discrete model of small unmanned helicopter with unknown parametersis determined by Takagi Sugeno system. Secondly, derivative based gradientmethod is used to identify unknown parameters of TS fuzzy model because in gradientadaptation, fuzzy system is not supposed to be linear in the parameters, so allfuzzy sets for input and output could be adjusted. The proposed method showedits effectiveness in terms of data matching obtained by the X-Plane©flight simulator. Obtained simulation results show high accuracy of themodeling method and better justification for real time applicability of theapproach DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3577